Pengaruh Financial Distress, Leverage, Fundamental Makro terhadap Kecurangan Laporan Keuangan - Helnisa Helnisa; Agus Zahron Idris (Pusat Riset dan Inovasi Nasional, 2026)
The study aims to analyze the influence of financial distress, leverage, and macroeconomic fundamentals on financial reporting fraud in state-owned enterprises (SOEs) listed on the Indonesia Stock Exchange (IDX) for the 2020–2024 period. A quantitative approach coupled with multiple linear regression analysis was employed. A saturated sampling technique was used to select 23 companies with 115 observation units. The data used were secondary data from published financial reports on the IDX. The results indicate that financial distress and macroeconomic fundamentals have no effect on financial reporting fraud, while leverage has a positive effect on financial reporting fraud. The model in this study is able to explain 6.9% of the variation in financial reporting fraud, while the remaining amount is influenced by factors outside the model. These findings indicate that companies with high debt levels are more likely to commit financial reporting fraud, while companies with financial problems and high interest rates are less likely to commit financial reporting fraud.